Covalently Binding Atomically Designed Au9 Clusters to Chemically Modified Graphene1. (6th July 2015) - Bosch‐Navarro, Concha; Laker, Zachary P. L.; Thomas, Helen R.; Marsden, Alexander J.; Sloan, Jeremy; Wilson, Neil R.; Rourke, Jonathan P.
Abstract Atomic‐resolution transmission electron microscopy was used to identify individual Au9 clusters on a sulfur‐functionalized graphene surface. The clusters were preformed in solution and covalently attached to the surface without any dispersion or aggregation. Comparison of the experimental images with simulations allowed the rotational motion, without lateral displacement, of individual clusters to be discerned, thereby demonstrating a robust covalent attachment of intact clusters to the graphene surface.